Kinetics of the Anaerobic Reaction of Para-Substituted Phenols with Nitrogen Dioxide - Lissi-Gervaso, E; Rubio-Campos, M; Reyes-Garcia, J (John Wiley and Sons Inc., 2017)
para-Substituted phenols in aqueous solution under anaerobic conditions readily react with nitrogen dioxide (NO2 ●) over a wide range of experimental conditions. The rate and rate law of the process were dependent on phenol concentration and solution pH. The kinetic order in phenol changed from one (low concentration) to zero (high concentration), a result attributable to total NO2 ● capture. Initial consumption rate (r0) of phenols versus pH plots showed parabolic behavior with a minimum rate at pH ca. 5. On the other hand, the maximum rate took place at high pH (pH>10) and involved the protonated phenols. The reaction rate of para-substituted phenols with NO2 ● correlated with the bond dissociation energy and with Hammett s parameter. Based on such results and also supported by analysis of products carried out by HPLC-MS/MS, our data conclusively show that, in spite of the fast acid–base interchanges of phenols and the interconversion of the different nitrogen oxides, the mechanisms of phenols nitration mediated by NO2 ● or HONO are clearly different. © 2016 Wiley Periodicals, Inc.